Engineering Safety Management System Based on Robot Intelligent Monitoring - Yanli Wang (Advances in Multimedia)
In order to improve the effect of engineering safety management, this paper combines intelligent monitoring technology to construct a monitoring robot system. Moreover, this paper analyzes the characteristics of the digital impulse signal and analyzes the least square filtering and infinite impulse response filtering. At the same time, this paper detects the sample material on the detection test platform, obtains the digital pulse signal, and selects different filtering algorithms and filtering parameters. In addition, this paper uses a signal analysis and processing platform to establish a gamma energy spectrum and analyze the resolution of hydrogen peaks in the gamma energy spectrum. Finally, this paper compares and verifies the filtering algorithms and constructs an engineering safety management system based on robot intelligent monitoring. From the simulation monitoring test results, it can be seen that the engineering safety management system based on robot intelligent detection proposed in this paper has a good effect.